Predicting negative health outcomes in older general practice patients with chronic illness: Rationale and development of the PROPERmed harmonized individual participant data database. (March 2021) - González-González, Ana I.; Dinh, Truc S.; Meid, Andreas D.; Blom, Jeanet W.; van den Akker, Marjan; Elders, Petra J.M.; Thiem, Ulrich; Kuellenberg de Gaudry, Daniela; Snell, Kym I.E.; Perera, Rafael; Swart, Karin M.A.; Rudolf, Henrik; et al.
Highlights: PROPERmed is the first study to combine data of older multimorbid patients from five trials. Individual participant data meta-analysis (IPD-MA) provide large samples/high-quality data. IPD-MA also require data harmonization which is labor intensive and may result in information loss. Future trials on multimorbidity/polypharmacy should collect more standardized data. Abstract: The prevalence of multimorbidity and polypharmacy increases significantly with age and are associated with negative health consequences. However, most current interventions to optimize medication have failed to show significant effects on patient-relevant outcomes. This may be due to ineffectiveness of interventions themselves but may also reflect other factors: insufficient sample sizes, heterogeneity of population. To address this issue, the international PROPERmed collaboration was set up to obtain/synthesize individual participant data (IPD) from five cluster-randomized trials. The trials took place in Germany and The Netherlands and aimed to optimize medication in older general practice patients with chronic illness. PROPERmed is the first database of IPD to be drawn from multiple trials in this patient population and setting. It offers the opportunity to derive prognostic models with increased statistical power for prediction of patient-relevant outcomes resulting from the interplay of multimorbidity and polypharmacy. This may help patients from this heterogeneous group to be stratified according to risk and enable clinicians to identify patients that are likely to benefit most from resource/time-intensive interventions. The aim of this manuscript is to describe the rationale behind PROPERmed collaboration, characteristics of the included studies/participants, development of the harmonized IPD database and challenges faced during this process.